TGR5 contributes to hepatic cystogenesis in rodents with polycystic liver diseases through cyclic adenosine monophosphate/Gαs signaling. Issue 4 (26th August 2017) - Masyuk, Tatyana V.; Masyuk, Anatoliy I.; Lorenzo Pisarello, Maria; Howard, Brynn N.; Huang, Bing Q.; Lee, Pui‐Yuen; Fung, Xavier; Sergienko, Eduard; Ardecky, Robert J.; Chung, Thomas D.Y.; Pinkerton, Anthony B.; LaRusso, Nicholas F.
Abstract : Hepatic cystogenesis in polycystic liver disease is associated with increased levels of cyclic adenosine monophosphate (cAMP) in cholangiocytes lining liver cysts. Takeda G protein receptor 5 (TGR5), a G protein–coupled bile acid receptor, is linked to cAMP and expressed in cholangiocytes. Therefore, we hypothesized that TGR5 might contribute to disease progression. We examined expression of TGR5 and Gα proteins in cultured cholangiocytes and in livers of animal models and humans with polycystic liver disease. In vitro, we assessed cholangiocyte proliferation, cAMP levels, and cyst growth in response to (1) TGR5 agonists (taurolithocholic acid, oleanolic acid [OA], and two synthetic compounds), (2) a novel TGR5 antagonist (m‐tolyl 5‐chloro‐2‐[ethylsulfonyl] pyrimidine‐4‐carboxylate [SBI‐115]), and (3) a combination of SBI‐115 and pasireotide, a somatostatin receptor analogue. In vivo, we examined hepatic cystogenesis in OA‐treated polycystic kidney rats and after genetic elimination of TGR5 in double mutant TGR5 −/− ; Pkhd1 del2/del2 mice. Compared to control, expression of TGR5 and Gαs (but not Gαi and Gαq ) proteins was increased 2‐fold to 3‐fold in cystic cholangiocytes in vitro and in vivo . In vitro, TGR5 stimulation enhanced cAMP production, cell proliferation, and cyst growth by ∼40%; these effects were abolished after TGR5 reduction by short hairpin RNA. OA increased cystogenesis in polycystic kidney rats by 35%; in contrast, hepatic cystic areas were decreased by 45% in TGR5‐deficient TGR5 −/− ;Pkhd1 del2/del2 mice. TGR5 expression and its colocalization with Gαs were increased ∼2‐fold upon OA treatment. Levels of cAMP, cell proliferation, and cyst growth in vitro were decreased by ∼30% in cystic cholangiocytes after treatment with SBI‐115 alone and by ∼50% when SBI‐115 was combined with pasireotide. Conclusion: TGR5 contributes to hepatic cystogenesis by increasing cAMP and enhancing cholangiocyte proliferation; our data suggest that a TGR5 antagonist alone or concurrently with somatostatin receptor agonists represents a potential therapeutic approach in polycystic liver disease. (Hepatology 2017;66:1197‐1218).